Pendidikan Kristen Sebagai Upaya Mengatasi Degradasi Moralitas dan Mereduksi Sikap Acuh Generasi Penerus terhadap Agama - Yonatan Alex Arifianto (Institut Agama Kristen Negeri Kupang, 2023)
Weak religious education and parental negligence in educating children, as well as the influence of gadgets and sophisticated technology in the digital era. And fragile family resilience can trigger the moral degradation of the next generation. Using descriptive qualitative methods with a literature study approach, it can be concluded that Christian education as an effort to overcome the degradation of morality and reduce the indifferent attitude of the next generation towards religion, must be done seriously for Christian churches and families in packaging Christian education as the main curriculum or teaching to reduce moral decline. The family can provide a paradigm for future generations of the impact of moral degradation on the church and state. This can be identified from an indifferent attitude towards religion and positive law as an indicator of the degradation of morality and the importance of Christian education. So Christianity, namely the church and the family, must be able to actualize the principles and values of Christianity and the role of the church as part of overcoming massive moral degradation for the next generation who will carry on the baton of leadership